2011
DOI: 10.1097/phm.0b013e318214de26
|View full text |Cite
|
Sign up to set email alerts
|

Applicability and Effects of Physical Exercise on Physical and Cognitive Functions and Activities of Daily Living Among People With Dementia

Abstract: : Among older people with Alzheimer disease in residential care facilities, combined functional weight-bearing exercise seems applicable for use regarding attendance and adverse events, and there is some evidence that exercise improves walking performance and reduces the decline in activities of daily living. Furthermore, there is some evidence that walking exercise performed individually reduces decline in walking performance, but adverse events need to be evaluated. Among older people with various types of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
111
1
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(126 citation statements)
references
References 74 publications
12
111
1
2
Order By: Relevance
“…However, according to Forbes et al 14 there is insufficient evidence to determine the effectiveness of physical activity programs in managing or improving cognition. In a recent systematic review, Littbrand et al 9 concluded that low methodological quality and/or an intervention of insufficient intensity can be responsible for the exercise has no effect on cognitive functions among people with dementias. These effects are dependent, however, on the intensity and frequency of exercise.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…However, according to Forbes et al 14 there is insufficient evidence to determine the effectiveness of physical activity programs in managing or improving cognition. In a recent systematic review, Littbrand et al 9 concluded that low methodological quality and/or an intervention of insufficient intensity can be responsible for the exercise has no effect on cognitive functions among people with dementias. These effects are dependent, however, on the intensity and frequency of exercise.…”
mentioning
confidence: 99%
“…Whereas studies which used walking as a type of aerobic intervention in patients with dementia did not provide the same results 8,12,13 . In recent years, several systematic reviews have observed positive effects of physical exercise on people with dementia 3,9 . However, according to Forbes et al 14 there is insufficient evidence to determine the effectiveness of physical activity programs in managing or improving cognition.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…While several recent systematic reviews on the effectiveness of exercise for cognitively impaired older adults exist (Burge, Kuhne, Berchtold, Maupetit, & von Gunten, 2012;Hauer et al, 2006;Heyn et al, 2004;Littbrand et al, 2011;Pitkala, Savikko, Poysti, Strandberg, & Laakkonen, 2013;Suttanon et al, 2011;Van Uffelen, Chin A Paw, Hopman-Rock, & Van Mechelen, 2008), all had their limitations. Only four of these reviews were specific to a dementia diagnosis, two of these only examined the effect on activities of daily living (ADLs) (Burge et al, 2012), with this considered a too narrow scope of physical function in this population and one was not specific on physical exercise (Littbrand et al, 2011;Suttanon et al, 2011). One recent systematic review (Pitkala et al, 2013) examined the effects of exercise interventions on mobility and physical function in people with dementia.…”
Section: = Equation 2: True Score Equation (Raykov and Marcoulides 201mentioning
confidence: 99%
“…Exercise undertaken regularly can have pronounced physical and functional benefits for adults with dementia (Ahlskog et al, 2011;Littbrand, Stenvall, & Rosendahl, 2011). To understand these benefits, we are reliant on the sound psychometric properties of the measures utilised to assess functional and physical capacity.…”
Section: Introductionmentioning
confidence: 99%